The reason I jump : the inner voice of a thirteen-year- old boy with autism - Higashida, Naoki, 1992-; Yoshida, KA.; Mitchell, David (David Stephen) (London : Sceptre, 2013)
A one-of-a-kind memoir that demonstrates how an autistic mind thinks, feels, perceives, and responds in ways few of us can imagine.
"Originally published in Japanese by Escor Publishers Ltd. in 2007"--Title page verso.
Keywords: Higashida, Naoki, -- 1992-; Autistic people -- Japan -- Biography; Autistic people -- Psychology; Autism